The gefitinib long-term responder (LTR) - a cancer stem-like cell story?: Insights from molecular analyses of German long-term responders treated in the IRESSA expanded access program (EAP) - Gottschling, Sandra; Herpel, Esther; Eberhardt, Wilfried E. E.; Köhne, Claus-Henning; Kuhnt, Thomas; Muley, Thomas; Meister, Michael; Bischoff, Helge; Schnabel, Philipp Albert; Thomas, Michael; Penzel, Roland (Lung cancer, 2012)
Background: In selected patients with advanced non-small cell lung cancer (NSCLC) the EGFR (epidermal growth factor receptor) tyrosine kinase inhibitor (TKI) gefitinib (IRESSA) shows response rates of ≥70% and a significant prolongation of progression free survival (PFS). However, cogent biomarkers predicting long-term response to EGFR-TKIs are yet lacking. Cancer stem-like cells (CSC) are thought to play a pivotal role in tumor regeneration and appear to be influenced by the EGFR-pathway. This makes them a promising candidate for predicting long-term response to EGFR-TKIs. Materials and methods: We analyzed pre-therapeutic tissue specimens of a rare and specific subset of previously treated German patients with advanced NSCLC who experienced ≥3 year response to gefitinib within the International IRESSA EAP. 11/20 identified long-term responders (LTRs) had appropriate tissue specimens available. Those were analyzed for EGFR and k-ras (Kirsten rat sarcoma) mutations, EGFR and c-met (met proto-oncogene) amplifications and protein expression of EGFR, E-cadherin/vimentin and the CSC antigens CD133 and BCRP1 (breast cancer resistance protein 1). The results were compared to primary resistant patients (RPs) and intermediate responders (IRs) showing a median response of 8.6 months. Results: Each group consisted of 6 women and 5 men, with 1 squamous cell carcinoma (SCC) and 10 adenocarcinoma (AC). Along the LTRs, all but the SCC had EGFR mutations, whereas the RPs had no EGFR, but k-ras mutations in 5/11 cases. 8/11 IRs had EGFR and 3/11 k-ras mutations, of which 2 occurred concomitantly. One patient of each group had an EGFR and/or c-met amplification. EGFR and E-cadherin/vimentin expression was not different between the groups, whereas CD133 was expressed only in 4/10 LTRs and BCRP1 predominantly in responders. The LTRs showed a substantially longer mean PFS to previous therapies, a substantially lower number of metastatic sites and almost exclusively pulmonary or pleural metastasis. Conclusion: LTRs display established properties of EGFR-TKI responders. Antigens characterizing CSC might identify a fraction of LTRs and matter of interest for further evaluation.
Gesehen am 17.04.2018